2021
DOI: 10.3390/s21227713
|View full text |Cite
|
Sign up to set email alerts
|

Elements Influencing sEMG-Based Gesture Decoding: Muscle Fatigue, Forearm Angle and Acquisition Time

Abstract: The surface Electromyography (sEMG) signal contains information about movement intention generated by the human brain, and it is the most intuitive and common solution to control robots, orthotics, prosthetics and rehabilitation equipment. In recent years, gesture decoding based on sEMG signals has received a lot of research attention. In this paper, the effects of muscle fatigue, forearm angle and acquisition time on the accuracy of gesture decoding were researched. Taking 11 static gestures as samples, four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…For the selection of classification models, LDA and SVM models were widely applied in HMI based on gesture recognition of their simple structure, high computational efficiency, and robustness [36]- [38]. This paper chose LDA and SVM (polynomial kernel) to classify different gestures and force levels.…”
Section: F Classification Modelmentioning
confidence: 99%
“…For the selection of classification models, LDA and SVM models were widely applied in HMI based on gesture recognition of their simple structure, high computational efficiency, and robustness [36]- [38]. This paper chose LDA and SVM (polynomial kernel) to classify different gestures and force levels.…”
Section: F Classification Modelmentioning
confidence: 99%
“…Typically, there is some period of time given to transition between gestures, which is flagged with a ‘Null’ label. This allows for three primary sources of error in labelling (i) users do not instantaneously transition between gestures and as a result many of the ‘Null’ samples will be members of actual gesture classes, (ii) user fatigue can lead to variation in production of gestures confounding a trained model [ 7 , 8 , 14 , 15 ], (iii) users may inadvertently make incorrect gestures [ 8 , 16 ]. The solutions presented in this paper focus on the first two issues.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 75% of the samples in a given data set can be ‘Null’ gestures which do not a gesture category included in the model [ 17 ]. The majority of contemporary studies reviewed for this paper indicated they discarded transient data in beginning/in between/at end of gestures, or indicated that transitions between gestures received some manual processing [ 8 , 9 , 10 , 11 , 12 , 15 ]. This can lead to unrealistically optimistic performance estimates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations